1951
DOI: 10.1002/jctb.5010010606
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry of phenolic resins and the processes leading to their formation

Abstract: The paper presents first a review of the work on phenolic resins done by Euler and his co‐workers, by Hultzsch and by Zinke and his team, and of the importance of this work for the knowledge of the hardening process. More recent research work of Zinke and his co‐workers, especially on cyclic polynuclear phenols is also described. There is a short discussion of the chemistry of novolaks and of the work of Ziegler. Results of research on the hexamine‐hardening process are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1958
1958
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…Moreover, the presence of the strong electron withdrawing group, -SO 3 CF 3 , in the mesopores of OMR-[C 3 HMTA][SO 3 CF 3 ] would be also helpful for improving the stability of polymeric network to some extent. [40][41][42][43]53 The superior stability of OMR- This journal is © The Royal Society of Chemistry 2012…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the presence of the strong electron withdrawing group, -SO 3 CF 3 , in the mesopores of OMR-[C 3 HMTA][SO 3 CF 3 ] would be also helpful for improving the stability of polymeric network to some extent. [40][41][42][43]53 The superior stability of OMR- This journal is © The Royal Society of Chemistry 2012…”
Section: Resultsmentioning
confidence: 99%
“…We demonstrate here a high temperature (200 °C) hydrothermal synthesis of strong acidic ionic liquids functionalized, ordered and stable mesoporous resins (OMR-ILs) for the first time, the high synthesis temperature will be helpful for obtaining the samples with a high cross-linking degree, resulting in their extra-ordinary thermal and mechanical stabilities as compared with the samples (FUD type of mesoporous polymers) synthesized at lower temperature (≤100 °C). [41][42][43][44][45] Generally, the synthesis of OMR-ILs was carried out by treating hexamethyltetramine (HMTA) crosslinked ordered and stable mesoporous resin (OMR-[HMTA]) using 1,3-propanesultone, ion exchanging using various strong acids. The performed OMR-[HMTA] could be synthesized from the self assembly of copolymer template of F127 with resol in the presence of hexamethyltetramine (HMTA) cross-linker under high temperature hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In phenolic/resole blends the etherification reaction between the methylol groups always prevails at 120-130 3 C as depicted in reaction 1(a) in figure 1. As the cure progresses at higher temperatures, further cross-linking takes place at 160 3 C. Zinke [12] showed that, above this temperature ether bridges begin to convert to methylene bridges by forming a quinone methide structure as shown in reaction 1(c) in figure 1. Tencher et al [14] substantiated the existence of the quinone methide structure through IR spectroscopic evidence.…”
Section: Infrared Analysismentioning
confidence: 99%
“…over similar time-scales and at similar temperatures. This is even more of a challenge with UP or VE and conventional phenolic resins owing to the different curing mechanisms of these two resins: phenolics cure by condensation reactions with the elimination of water (incompatible with UP and VE) and formaldehyde at temperatures of up to 180-200 ˚C [27], whilst UP and VE resins cure with styrene by a free radical process at temperatures typically below 80 ˚C [28]. Thus, whilst mixtures of low molecular weight resin precursors may be miscible, once chain extension and crosslinking begins, immiscibility may develop leading to significant phase separation and resulting in brittle, non-homogeneous, blends.…”
Section: Introductionmentioning
confidence: 99%